A neuromorphic robotic electronic skin with active pain and injury perception - Yuyu Gao; Jianpeng Zhang; Hehua Zhang; Lung Chow; Guangyao Zhao; Guihuan Guo; Chun Ki Yiu; Binbin Zhang; Ya Huang; Jingkun Zhou; Qiang Zhang; Tao Huang; et al. (Proceedings of the National Academy of Sciences, 2025)
Humanoid robots with advanced sensory capabilities are increasingly demanded for empathetic, close-contact interactions with humans. Electronic skin (E-skin) is a key enabling technology for such tactile perception. However, current E-skins are limited to basic tactile sensing with simple circuit architecture. Here, we introduce a neuromorphic robotic e-skin (NRE-skin) that not only provides fundamental tactile sensing but also integrates advanced features, such as active pain and injury detection. The NRE-skin encodes dynamic tactile stimuli into neural-like pulse trains and features active pain detection that triggers protective reflexes. Additionally, its injury sensing and modular design enable precise localization of damaged areas and rapid replacement of affected skin. By emulating human sensory and protective systems, the NRE-skin facilitates more natural and safer human–robot interactions.